Analyzing Supply Chain Resilience In Response To Supplier Level Disruptions Using The Gscor Method (Case Study: Assessing Supplier Performance At Pt. Trakindo Surabaya) - Asya Fadhilah Adistara; Farida Pulansari; Nur Rahmawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Currently, environmental issues are largely connected to corporations that typically depend on complicated and extensive supply chains. At PT. TRAKINDO Surabaya, raw materials are housed in expansive storage facilities situated outside the city and at a considerable distance. This setup leads to significant carbon emissions from the vehicles used to transport these materials. PT. TRAKINDO Surabaya serves as an authorized distributor of heavy equipment from Caterpillar, a premier American manufacturer with a presence in industries such as mining, construction, oil and gas, forestry and agriculture, and power systems. In the industrial arena, global competition is intensifying as consumer demands escalate. Supply chain management can now be categorized into two kinds: conventional management, which primarily aims to raise value, and eco-friendly supply chain management. Consequently, a thorough analysis of different production facets is required, considering aspects like production, suppliers, and procurement. The GSCOR method is one such approach that can be adopted. This study introduces refreshing insights by offering recommendations to address challenges with suppliers, including delivery delays, constrained delivery capacity, price volatility of raw materials, and material quality concerns. These initiatives seek to enhance each supplier's efficiency at PT. TRAKINDO Surabaya and support the company in minimizing waste from production remains